O desvio reprodutivo se correlaciona positivamente com o parentesco genético e o sistema de acasalamento? Euglossa cordata (Hymenoptera, Apidae, Euglossini) como estudo de caso - Freiria, Gabriele Antico (2015)
The orchid bees have always been considered promising for studies of the evolution of social behavior and reproductive division of labor. This is due to the fact that the orchid bees are the only members not clearly eusocial in corbiculate clade. In this study, the correlation between genetic relatedness and reproductive skew was investigated in the genus Euglossa, one of the five genus of Euglossini tribe, in order to support the understanding of the evolution of reproductive division of labor in Euglossini. Among the five genera of Euglossini, Euglossa is the most suitable for studies on the evolution of reproductive division of labor, because in this genus can be found solitary, communal and primitively eusocial species. Twelve nests of Euglossa cordata (Linnaeus, 1758) were analyzed. In this species, the foundation process is solitary, but small colonies are formed during nest reactivations, with females establishing different types of associations, in which their relatedness differs. During reactivations, one of the females performs oophagy and then oviposition in brood cells previously operculated by another females, consequently leaving a larger number of offspring. The behavioral analysis associated with relatedness estimates, made through the use of microsatellite markers, indicated that the dominant female perform oophagy followed by oviposition in all operculated cells by the subordinated bees. The reproductive skew was complete, regardless of the type of association established between the interacting females, and so reproductive skew and genetic relatedness was not associated in this study. Furthermore, the nesting biology of Euglossa was also studied, given the information scarcity about the nesting process in most species already described for this genus. Using the technique of trap nests, 43 nests of Euglossa were sampled. This study provides new information on the nesting biology of this genus, especially with regard to natural enemies associated with nests.